POST-OPERATIVE SENSITIVITY IN COMPOSITES USING BULK-FILL VS. OBLIQUE INCREMENTAL PLACEMENT TECHNIQUE: A DOUBLE-BLIND, RANDOMIZED TRIAL - Amir, Nehal; Mansoor, Hashim Bin; Rizwan, Haider; Ijaz, Ayman; Hussain, Khadim (Journal of Ayub Medical College Abbottabad, 2025)
Background Post-operative sensitivity is a potential drawback of composite restorations. Placement strategies have a profound impact on sensitivity. This trial is aimed to compare the occurrence and severity of sensitivity in composites using bulk-fill technique and oblique incremental technique. Methods This double-blind, randomized clinical trial was conducted at the Department of Operative Dentistry and Endodontics, School of Dentistry, Islamabad from December 20, 2022, to July 24, 2023. A total of 90 participants with moderate-sized Class II carious lesions were recruited and randomly distributed into two groups A and B (n=45). After informed consent, restorative intervention was accomplished using an etch-and-rinse adhesive strategy. In group A, a nanohybrid composite resin was placed using an oblique incremental strategy with a thickness of 2 mm while in group B, bulk-fill strategy was employed with a thickness of 4 mm. Participants were instructed to rate their sensitivity status at evaluation periods using Visual analogue scale. Data was analyzed using the Independent Sample T-test. The level of significance was calibrated at ≤0.05. Results According to results of this trial, a significant difference was discerned between two groups after one day (p=0.00) and one week (p=0.01). Nonetheless, the statistical contrast between two groups was not as significant (p=0.05) after two weeks period. Conclusion In conclusion, post-operative sensitivity at all three-time intervals using Bulk-fill technique was reported to be less than Oblique incremental approach. This corroborates the claim that utilizing the bulk-fill strategy for composite restoration mitigates post-operative discomfort.